A case of palisaded neutrophilic and granulomatous dermatitis associated with systemic lupus erythematosus presenting with pustules. Issue 2 (11th October 2022) - Tajima, Aki; Yamazaki, Fumikazu; Huynh, Trang Nguyen Mai; Ueda‐Hayakawa, Ikuko; Kishimoto, Izumi; Itsukage, Shizu; Kume, Noriko; Tanizaki, Hideaki
Abstract: Palisaded neutrophilic and granulomatous dermatitis (PNGD) is a relatively rare skin disease that is characterized by a reactive granulomatous histopathological pattern and is often associated with systemic autoimmune diseases. We encountered a case of PNGD that presented with pustules, although the prototypical clinical presentation of PNGD is mainly erythema and papules. Here, this rare case of PNGD with pustules is presented and discussed in relation to the relevant literature.